2013
DOI: 10.1155/2013/479505
|View full text |Cite
|
Sign up to set email alerts
|

Berry and Citrus Phenolic Compounds Inhibit Dipeptidyl Peptidase IV: Implications in Diabetes Management

Abstract: Beneficial health effects of fruits and vegetables in the diet have been attributed to their high flavonoid content. Dipeptidyl peptidase IV (DPP-IV) is a serine aminopeptidase that is a novel target for type 2 diabetes therapy due to its incretin hormone regulatory effects. In this study, well-characterized anthocyanins (ANC) isolated from berry wine blends and twenty-seven other phenolic compounds commonly present in citrus, berry, grape, and soybean, were individually investigated for their inhibitory effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
153
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(165 citation statements)
references
References 29 publications
10
153
1
1
Order By: Relevance
“…To validate the crystal structure of the ligand, the docking was carried out in 100 genetic algorithm runs, and the remaining genetic algorithm parameters were maintained at their default values. The optimal docking results were obtained when the lowest binding energy (∆G) in the conformation was reached by using the following equation (FAN et al, 2013):…”
Section: Molecular Modelling and Computational Docking Studymentioning
confidence: 99%
“…To validate the crystal structure of the ligand, the docking was carried out in 100 genetic algorithm runs, and the remaining genetic algorithm parameters were maintained at their default values. The optimal docking results were obtained when the lowest binding energy (∆G) in the conformation was reached by using the following equation (FAN et al, 2013):…”
Section: Molecular Modelling and Computational Docking Studymentioning
confidence: 99%
“…Therefore, Gram-negative bacteria are resistant to the extract of crowberry fruit. Epidemiological studies have suggested that edible berries are beneficial in reducing the risk of type-2 diabetes [27,28] . To identify the potential of crowberry fruit as an antidiabetic supplement, crude 70 % ethyl alcohol extract and its fractions were tested for α-glucosidase and α-amylase inhibitory activities.…”
Section: Resultsmentioning
confidence: 99%
“…Cyanidin 3, 5-diglucoside in aronia juice fraction was found as the main component to act as a DPP IV inhibitor. It has been reported that phenolic compounds such as cyanidin, cyanidin-3-glucocide, malvidin, luteolin, apigenin, quercetin, kaempferol, hesperetin, naringenin, eriocitrin, genistein, resveratrol, gallic acid and caffeic acid are DPP IV inhibitors in berries and citrus fruit [17]. In food protein hydrolysates, DPP IV inhibitors have been reported to be derivative peptides from atlantic salmon skin, tuna cooking juice, Japanese rice bran, gouda cheese and milk protein [18].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also shown that aronia juice contains anthocyanin glycosides including cyanidin 3-galactoside, cyanidin 3-arabinoside, cyanidin 3-gulcoside and cyanidin 3-xyloside [19][20][21][22][23][24]. Furthermore, cyanidin and cyanidin 3-glucoside have been reported to be DPP IV inhibitors [17]. We found that DPP IV activity was inhibited more strongly by cyanidin 3, 5-diglucoside than by cyanidin and cyanidin 3-glucoside, which have been reported to be DPP IV inhibitors.…”
Section: Discussionmentioning
confidence: 99%